Motivations for substance abusers: A qualitative study - Hassan Mokhtarpour; Mohammad Ali Goodarzi; Mohammad Reza Taghavi; Aliakbar Faghihi (مجله علوم روانشناختی, 2021)
Background: Substance abuse represents one of the major concerns in developing countries such as Iran. On the other hand, most previous research has been on the motivations for substance abuse in local samples and younger age groups (eg adolescents), and as a result our knowledge of the motivations for substance abuse in adults is limited. Aims: The purpose of this study was to identify the motives behind substance abuse from the perspectives of abusers, their families, and experienced mental health specialists in Shiraz city, Iran. Methods: Phenomenological qualitative method was used to conduct the research. The data were collected through semi-structured interviews based on the theoretical sampling method. The participants were 26 individuals including five addiction specialists/therapists, one family members of abusers, and 19 substance abusers. The interviews were recorded and then transcribed. The interviews were then constantly compared based on qualitative content analysis. Results: Out of 943 initial codes, 10 main categories and 24 sub-categories were extracted that described the “motives for substance abuse.” The main categories were “communication problems”, “physical problems”, “attitude toward addiction”, “experiential avoidance”, “two-wolves” (excessive pleasure-seeking by taking both alcohol and narcotics), “addictive behaviors”, “social determinants”, “psychiatric disorders”, “cultural issues”, and “genetic issues”. Conclusion: The motives for substance abuse involved a wide range of biological, psychological, and social determinants, which must be addressed in addiction prevention programmes. Further research must probe into the effective processes of such factors.